PENINGKATAN KETERAMPILAN MENULIS LAPORAN PERCOBAAN MENGGUNAKAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Rizky Amelia (Universitas Negeri Padang, 2018)
This study aims to explain the improvement of experimental report writing skills using a scientific approach in thematic learning in class IV SD Negeri 15 Ulu Gadut, Pauh District, Padang City. This study uses quantitative and qualitative approaches. This type of research is a classroom action research conducted in two cycles, consisting of planning, implementing, observing, and reflecting on each cycle. The subject of the study consisted of 36 teachers and students of SDU 15 Ulu Gadut, Pauh City, Padang. The results showed that: the application of the scientific approach to learning to write experimental reports was able to: motivate students to learn to write in real terms because they collected their own data from the object or phenomenon of the experiment that would be written; students feel challenged to explore their curiosity about natural phenomena; please students because they feel proud to be able to participate in writing activities; arouse students' writing interest because they can publish the results of their experiments in writing.Keywords: report writing, thematic, scientific